O dwóch imionach chrześcijańskich u osób świeckich w starorosyjskiej antroponimii XV–XVII wieku - Wójtowicz, Marian (Slavia Orientalis, 2024)
The article concerns the issue of two Christian names given to a single person in the 15th-17th centuries. The first name was given at baptism and, according to the religious ritual, it was a single name. It was called the prayer name (molitvennoye imya) or the true, real name (pryamoye imya). This name was obligatory but was often omitted in documents. The second Christian name was chosen and given by parents or relatives and was commonly used. In sources, it is referred to as a nickname (prozvishche, prozvaniye). This was an optional name. The author discusses the status and functions of both names, the relationship between them, and the church calendar. The second name among representatives of the upper classes led to changes in the status and functioning of the first name. It was socially approved and used as the official name. In the names of people from lower social classes, it was an additional name used to identify a person within a small communicative community. This was also an optional name, which, however, did not cause changes in the functioning of the first name.